Graves’ ophthalmopathy: Low-dose dexamethasone reduces retinoic acid receptor-alpha gene expression in orbital fibroblasts - Cury, Sarah Santiloni [UNESP]; Oliveira, Miriane [UNESP]; Síbio, Maria Teresa [UNESP]; Clara, Sueli [UNESP]; Luvizotto, Renata De Azevedo Melo [UNESP]; Conde, Sandro; Jorge, Edson Nacib [UNESP]; Nunes, Vania Dos Santos [UNESP]; Nogueira, Célia Regina [UNESP]; Mazeto, Gláucia Maria Ferreira da Silva [UNESP] (Archives of Endocrinology and Metabolism, 2018)
Objective: Graves’ ophthalmopathy (GO) is an autoimmune disease that leads to ocular proptosis caused by fat accumulation and inflammation, and the main treatment is corticosteroid therapy. Retinoid acid receptor-alpha (RARα) seems to be associated with inflammation and adipocyte differentiation. This study aimed to assess the effect of glucocorticoid treatment on orbital fibroblasts of GO patient treated or not with different glucocorticoid doses. Materials and methods: Orbital fibroblasts collected during orbital decompression of a female patient with moderately severe/severe GO were cultivated and treated with 10 nM and 100 nM dexamethasone (Dex). RARα gene expression in the treated and untreated cells was then compared. Results: Fibroblast RARα expression was not affected by 100 nM Dex. On the other hand, RARα expression was 24% lower in cells treated with 10 nM Dex (p < 0.05). Conclusions: Orbital fibroblasts from a GO patient expressed the RARα gene, which was unaffected by higher, but decreased with lower doses of glucocorticoid.
Keywords: Gene expression; Graves ophthalmopathy; Receptors; Retinoic acid